Evaluation of an Education Strategy versus Usual Care to Implement the STEADI Algorithm in Primary Care Clinics in an Academic Medical Center - Urban K (Dove Medical Press, 2020)
Kelly Urban,1 Patricia B Wright,1 Amy L Hester,1,2 Geoffrey Curran,3 Martha Rojo,1 Pao-Feng Tsai4 1College of Nursing, University of Arkansas for Medical Sciences, Little Rock, Arkansas, USA; 2HD Nursing, Bauxite, Arkansas, USA; 3College of Pharmacy, University of Arkansas for Medical Sciences, Little Rock, Arkansas, USA; 4School of Nursing, Auburn University, Auburn, Alabama, USACorrespondence: Kelly UrbanCollege of Nursing, University of Arkansas for Medical Sciences, 4301 West Markham Street, Slot 526, Little Rock, Arkansas 72205, USATel +1 501-416-3895Fax +1 501-686-7942Email klurban@uams.eduBackground: Although falls are the leading cause of morbidity and mortality in the US in the older adult population, there is little information regarding implementation of evidence-based fall prevention guidelines within primary care settings. The objective of this study was to address this gap in the literature by determining the effectiveness of the use of education and written materials as implementation strategies.Methods: Using a prospective, mixed methods, controlled before-and-after study design, we studied the effect of the Stopping Elderly Accidents, Deaths, and Injuries (STEADI) education and written materials on knowledge and intention to use in primary care clinics as well as test the screening, assessment, and intervention behaviors. This manuscript details the quantitative findings of the study, using STEADI Knowledge Test, Continuing Professional Development (CPD) Reaction Questionnaire, and EMR Reports. We compared data between the study arms (usual implementation versus education implementation) using descriptive statistics, paired t-tests, and factorial ANOVAs.Results: In total, data from 29 primary care staff, including physicians, APRNs, RNs, and medical assistants, were analyzed. Although we found a statistically significant difference within the education arm between immediate pretests and posttests/surveys mean scores, there was no statistically significant difference between the study arms’ knowledge, intent to use STEADI, or use behaviors. The pre/immediate post education mean knowledge score increased by 1.19 (p= 0.02) and the pre/immediate post education intent to use mean increased by 0.64 (p 0.01). There was no statistically significant change between the study arms over time.Conclusion: Educational strategies, particularly written materials and an online module, did not increase the long-term use of the STEADI toolkit. Implementation research is needed to identify the strategies that are most effective for promoting the adoption of STEADI in primary care.Keywords: STEADI toolkit, implementation, primary care providers